Benefits in the macrophage response due to graphene oxide reduction by thermal treatment - Cicuéndez, Mónica (2021)
Graphene and its derivatives are very promising nanomaterials for biomedical applications and are proving to be very useful for the preparation of scaffolds for tissue repair. The response of immune cells to these graphene-based materials (GBM) appears to be critical in promoting regeneration, thus, the study of this response is essential before they are used to prepare any type of scaffold. Another relevant factor is the variability of the GBM surface chemistry, namely the type and quantity of oxygen functional groups, which may have an important effect on cell behavior. The response of RAW-264.7 macrophages to graphene oxide (GO) and two types of reduced GO, rGO15 and rGO30, obtained after vacuum-assisted thermal treatment of 15 and 30 min, respectively, was evaluated by analyzing the uptake of these nanostructures, the intracellular content of reactive oxygen species, and specific markers of the proinflammatory M1 phenotype, such as CD80 expression and secretion of inflammatory cytokines TNF-α and IL-6. Our results demonstrate that GO reduction resulted in a decrease of both oxidative stress and proinflammatory cytokine secretion, significantly improving its biocompatibility and potential for the preparation of 3D scaffolds able of triggering the appropriate immune response for tissue regeneration.